2020
DOI: 10.1044/2020_persp-19-00155
|View full text |Cite
|
Sign up to set email alerts
|

Early Achievements for Education Settings: An Embedded Teacher-Implemented Social Communication Intervention for Preschoolers With Autism Spectrum Disorder

Abstract: Purpose Early Achievements for Education Settings (EA-ES) is a teacher-implemented naturalistic developmental behavioral intervention for preschoolers with autism spectrum disorder (ASD) targeting core social communication impairments. The purpose of this pilot randomized controlled clinical trial (RCT) was to examine promise of efficacy of this iteratively developed intervention when implemented in authentic education settings. We examined (1a) whether a high level of implementation fidelity was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…The PD program targeted providers’ implementation of selected NDBI strategies and use of book-related props to create embodied child social-communication learning experiences (Landa et al, 2011 ) embedded within book reading instruction (Schreibman et al, 2015 ). This intervention was translated for use in inclusive child care classrooms from its initial iteration in preschool classrooms serving children with ASD (Engelstad et al, 2020 ) and in a clinic-based intervention for toddlers with ASD (Landa et al, 2011 ). The EA-CP PD consisted of a combination of workshops and coaching.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PD program targeted providers’ implementation of selected NDBI strategies and use of book-related props to create embodied child social-communication learning experiences (Landa et al, 2011 ) embedded within book reading instruction (Schreibman et al, 2015 ). This intervention was translated for use in inclusive child care classrooms from its initial iteration in preschool classrooms serving children with ASD (Engelstad et al, 2020 ) and in a clinic-based intervention for toddlers with ASD (Landa et al, 2011 ). The EA-CP PD consisted of a combination of workshops and coaching.…”
Section: Methodsmentioning
confidence: 99%
“…To promote high-fidelity implementation, our PD program focused on a key instructional context in early childhood curricula (Lorio & Woods, 2020 ): shared book reading. Shared book reading provides an enriching context for teaching vocabulary (Toub et al, 2018 ; Wasik et al, 2016 ), which can be enhanced with opportunities for adult-supported play with book-related props (Toub et al, 2018 ) to increase engagement and language use, even in children with DD (Engelstad, Holingue, & Landa, 2020 ; Feuerstein & Landa, 2020 ). Further, book reading is often enjoyable (thus motivating and reinforcing) for both adults and children (Sim & Berthelsen, 2014 ).…”
Section: Practice-based Pdmentioning
confidence: 99%
“…However, this paper was developed by the members of a research network that used snowball-sampling procedures to identify leading programs (Siller et al, 2021). These programs include the Walden Early Childhood Center at Emory University (now the Early Emory Center for Child Development and Enrichment;McGee et al, 1999), Project DATA at the University of Washington (Boulware et al, 2006), Early Achievements at the Kennedy Krieger Institute (Engelstad et al, 2020;Feuerstein & Landa, 2020), Samsky Preschool at Marcus Autism Center/ Emory University (Siller et al, 2022), the Victorian Autism Specific Early Learning and Care Center affiliated with the Olga Tennison Autism Research Center at La Trobe University in Australia (Capes et al, 2019;Vivanti et al, 2019Vivanti et al, , 2022, the Children's Toddler School (now Alexa's PLAYC; Stahmer et al, 2011;Stahmer & Ingersoll, 2004), and the Susan Gray School at Vanderbilt University (Hine & Wolery, 2006).…”
Section: Past Efforts To Promote Inclusion Of Young Children With Dis...mentioning
confidence: 99%
“…( 2) NDBIs emphasize embedding learning activities within childchosen or child-preferred activities, which allows children to connect learning experiences to situations/materials that are relevant and interesting to them (Vivanti et al, 2022). ( 3) NDBIs leverage environmental arrangement, where adults arrange the learning environment to facilitate child initiation and allow children to experience the natural contingencies of their self-initiated behavior (Engelstad et al, 2020;Feuerstein & Landa, 2020). For example, NDBIs may create communication temptations by giving the child access to only half of the blocks in a container to facilitate initiations of requests to a peer for objects or assistance (Bruinsma et al, 2020).…”
Section: Teaching To Enhance Each Child's Development and Learningmentioning
confidence: 99%
“…Aligned with this emerging consensus from ECE professionals, researchers, and policy leaders, parent coaching is considered an essential element of successful early intervention for children with autism spectrum disorder (ASD; Nevill et al, 2018; Siller & Morgan, 2018). However, despite increased interest in adapting evidence-based interventions for children with ASD to school settings (Engelstad et al, 2020; Stahmer et al, 2015), to date, only two studies reported integrating ASD-specific parent coaching methods in center-based pre-K settings (Ingersoll & Dvortcsak, 2006; Ingersoll & Wainer, 2013). In both studies, Project ImPACT was implemented as part of children’s publicly funded, school-based early childhood special education (ECSE) program.…”
mentioning
confidence: 99%